Solar thermical equipments for the processing of agricultural and agroindustrial products in the Northern Huetar Region of Costa Rica: Local pilot program - Guzmán-Hérnandez, Tomás J. (2020)
Different energy sources are applied in the operations used for processing and preserving food and other agricultural products. The Technology Institute of Costa Rica and the agricultural sector of Costa Rica has supported the Local Pilot Program for the use of solar energy in the Northern Huetar Region of Costa Rica for the application and evaluation of different solar thermal systems in small and medium-sized agricultural units to replace the traditional methods of energy generation for clean production systems, reduce the local carbon footprint and improve production conditions. For this reason, in the Northern Huetar Region of Costa Rica, hybrid solar thermosiphonic systems with an auxiliary electric system have been designed and evaluated for the sterilization of milking equipment; hybrid solar thermal systems with water and LP gas for sterilization and pasteurization of milk; hybrid forced solar thermal systems with water, hot air and LP gas and a passive solar dryer for different types of agricultural products. The results of the evaluation of these systems were obtained by setting thermocouples in key places inside the systems and they were stored in the cybernetic space to facilitate their access through any electronic device. These results has allowed verify the decrease in operating costs related to energy bills, the efficiency improvement of the different processes and the carbon footprint decreasing of these farms, which would represent a competitive advantage in the regional, national and international markets.